Upper Palaeolithic Installation Art: Topography, Distortion, Animation and Participation in the Production and Experience of Cantabrian Cave Art. Issue 4 (November 2020) - Sakamoto, Takashi; Pettitt, Paul; Ontañon-Peredo, Roberto
Abstract : The physical nature of cave walls and its impact on Upper Palaeolithic image making and viewing has frequently been invoked in explanations about the function of cave art. The morphological features (convexities, concavities, cracks and ridges) are frequently incorporated into the representations of prey animals that dominate the art, and several studies have attempted to document the relationship between the cave wall and the art in a quantitative manner. One of the effects of such incorporation is that undulating walls will distort the appearance of images as viewers change their viewing position. Was this distortion deliberate or accidental? Until now, the phenomenon has not been investigated quantitatively. We address this here, analysing 54 Late Upper Palaeolithic animal images deriving from three Cantabrian caves, Covalanas, El Pendo and El Castillo. We introduce a novel use for photogrammetry and 3D modelling through documenting the morphology of these caves' walls and establishing the specific relationship between the walls and the art created on them. Our observations suggest that Palaeolithic artists deliberately placed images on very specific topographies. The restricted nature of these choice decisions and the fact that the resulting distortions could have been avoided but were not suggest that the interaction between viewer, art and wall was integral to the way cave art functioned.